1998
DOI: 10.1039/a707292i
|View full text |Cite
|
Sign up to set email alerts
|

Selenium speciation in human body fluids†

Abstract: Selenium consumed by humans in foods and in supplements exists in a number of different organic and inorganic forms including selenomethionine, selenocysteine, selenate and selenite. Animal and human studies have established that the bioavailability of the selenium depends upon the chemical form, which also influences the distribution of selenium in the body. These studies have included urinary excretion of selenium following ingestion of different forms of selenium and the response of tissue selenium concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 37 publications
1
74
0
7
Order By: Relevance
“…In agreement with other studies (19,20), which showed maximum GPx1 activity occurrs with selenium values higher than 100 ng/mL, we found that the serum selenium concentrations were higher than 213 ng/mL.…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with other studies (19,20), which showed maximum GPx1 activity occurrs with selenium values higher than 100 ng/mL, we found that the serum selenium concentrations were higher than 213 ng/mL.…”
Section: Discussionsupporting
confidence: 81%
“…The need to provide infant formulae which satisfy the dietary requirement for selenium just as human milk is doing, should prompt further speciation studies (51,52) …”
Section: Discussionmentioning
confidence: 99%
“…Daily urinary excretion is closely associated with plasma selenium and dietary intake in low selenium populations (Griffiths & Thomson, 1974), and, therefore, can be used to assess selenium status reflecting recent dietary intake. Balance studies show that over a wide range of intakes, urinary excretion accounts for 50-60% of the total amount excreted (Robinson et al, 1973), and therefore, total dietary intake can be estimated as twice the daily urinary excretion (Thomson, 1998).…”
Section: Biochemical Tests For Nutritional Status Of Seleniummentioning
confidence: 99%